Legacies of European 'Belt and Road'? Visualizing transport accessibility and its impacts on population distribution. Issue 1 (1st January 2019) - Zhou, Jiangping; Yang, Yuling; Webster, Chris
ABSTRACT: The 'Belt and Road Initiative' was announced in 2013 to better connect China economically, socially and culturally with the world by new transport infrastructures. Before forecasting the long-term impacts of the initiative on economic activities and population, one could learn from history about how transport infrastructures and the corresponding accessibility of different locales they engendered or enhanced might have shaped and reshaped the distribution of the population and economic activities in Europe. Historic maps of transport infrastructures and population statistics were collected from such sources as the Stanford Geospatial Network Model of the Roman World, the Perry-Castañeda Library Map Collection, and the Gridded Population of the World Version 4. By digitizing and synthesizing the maps and statistics, transport accessibility in Europe and its nearby areas was mapped during both the Roman Empire (27 BC–476 AD) and the Middle Ages (1000–1500 AD), as well as the population distribution in Europe and its nearby areas in 2015. The mapping efforts indicated that the transport network changed greatly over time for various reasons, and that transport accessibility is a sufficient but not necessary condition for different locales' population growth and economic prosperity over time.